Nasopharyngeal carcinoma detected noninvasively in the real world using three gene methylation analyses from automatically processed bilateral nasal swab samples - Zi-Han Qin; Si-Yuan Chen; Shuai Zhou; Hua Deng; Lan-Xi Li; Qi-Lun Guo; Xiong Zou; Pei-Yu Huang; Ming-Yuan Chen; Liang Zhang; Yi-Jun Hua (BMC Cancer)
Abstract Background Efforts have been made to improve the performance of nasopharyngeal carcinoma screening strategies, which include EBV related biomarkers. However, the advances achieved still remain imperfection. DNA methylation occurs early in cancer development and can be used as potential diagnostic biomarker. This study aimed to investigate the diagnostic performance of three methylated genes in nasopharyngeal carcinoma (NPC) patients. Methods A total of 255 nasopharyngeal swabs and 35 plasma samples were collected from patients with newly diagnosed or treated NPC and healthy controls. Methylation-specific PCR (MSP) was used to evaluate the methylation levels of three genes (SEPTIN9, RASSF1A, and H4C6) in swabs and plasma samples. The methylation rates, sensitivity, and specificity of the candidate genes were calculated. Furthermore, the detectability of methylated genes in paired swabs and plasma was compared. Results The detection rate of methylated SEPTIN9, RASSF1A, and H4C6 in nasopharyngeal swabs of patients with newly diagnosed NPC was 88.2%, 92.9% and 71.8%, respectively, while it reduced to 54.3%, 42.9% and 45.7% in blood plasma. The sensitivity of detecting methylated SEPTIN9, RASSF1A, and H4C6 to distinguish between untreated NPC and healthy controls was 88%, 93%, and 72%, respectively. Methylated RASSF1A showed the highest classification accuracy (AUC = 0.956). The detection rate of the methylated target genes was considerably lower in paired plasma samples. Conclusion The detection of RASSF1A methylation through non-invasive nasopharyngeal cavity swab sampling demonstrates significant potential for NPC diagnosis.